2020
DOI: 10.1111/age.12979
|View full text |Cite
|
Sign up to set email alerts
|

A nonsense variant in the KRT14 gene in a domestic shorthair cat with epidermolysis bullosa simplex

Abstract: Summary Epidermolysis bullosa simplex (EBS) is a hereditary blistering disease affecting the skin and mucous membranes. It has been reported in humans, cattle, buffaloes and dogs, but so far not in cats. In humans, EBS is most frequently caused by variants in the KRT5 or KRT14 genes. Here, we report a case of feline epidermolysis bullosa simplex and describe the causative genetic variant. An 11‐month‐old male domestic shorthair cat presented with a history of sloughed paw pads and ulcerations in the oral cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…EB is a rare disease also in the feline species, with few cases reported at the clinicopathological level. Previously reported cases were characterized by onychomadesis and localized or generalized skin and oral ulcerations, resulting in either mild or severe phenotypes, as seen in our cases [9,13,19,42]. A KRT14 variant was identified in a single cat with EBS [19].…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…EB is a rare disease also in the feline species, with few cases reported at the clinicopathological level. Previously reported cases were characterized by onychomadesis and localized or generalized skin and oral ulcerations, resulting in either mild or severe phenotypes, as seen in our cases [9,13,19,42]. A KRT14 variant was identified in a single cat with EBS [19].…”
Section: Discussionmentioning
confidence: 50%
“…Previously reported cases were characterized by onychomadesis and localized or generalized skin and oral ulcerations, resulting in either mild or severe phenotypes, as seen in our cases [9,13,19,42]. A KRT14 variant was identified in a single cat with EBS [19]. In another study involving two cats diagnosed with JEB, LAMC2 and LAMB3 were identified as possible candidate genes by indirect immunofluorescence, but the underlying genetics was not reported [13].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The resulting keratin filament network is connected to hemidesmosomes, which attach the basal keratinocytes to the underlying basement membrane (Walko et al., 2015). Genetic variants in KRT5 and KRT14 are known to represent the most frequent cause of epidermolysis bullosa simplex (EBS) in humans and animals alike (Bergson et al., 2023; Dettwiler et al., 2020; Kiener et al., 2022; Lane et al., 1992). EBS is the most widespread type of epidermolysis bullosa (Has et al., 2020).…”
Section: Figurementioning
confidence: 99%